Investigation and analysis of the current situation of research capacity of professional graduates majoring in neurosurgery - LIU Zhenlei, JIAN Fengzeng, WU Hao (Jichu yixue yu linchuang, 2024)
Objective In order to provide reference and basis for the scientific research capacity training of medical graduates, the current situation training for professional graduates majoring in neurosurgery was investigated and analyzed. Methods A questionnaire survey was conducted among graduates majoring in neurosurgery at Xuanwu Hospital. Possible relevant factors were analyzed, including scientific research awareness, scientific research initiative, scientific research interest, weekly science citation indexTM(SCI) literature reading, number of thesis published in Chinese core journals, number of thesis published in SCI journals, and participation in clinical and basic research project, number of registered clinical studies, experience in writing fund applications, supervisor′s scientific research requirements, participation in Journal Club activities. The current status of scientific research capacity building of graduates in our department and the factors of scientific research productivity were analyzed. Results Professional graduate majoring in neurosurgery had the highest weekly scientific research literature reading score (4.32±1.04), higher scientific research awareness, scientific research initiative, and scientific research interest scores (3.82-3.89).However, participation in scientific research (2.80±1.18) and thesis publication(2.50±1.52) were relatively low. Comparing graduates of different grades, scientific research awareness and initiative increase with raising grade. Most of first-year master candidates had the lowest scores in sum of relevant factors. In addition, the result of linear regression analysis suggested that scientific research interest and participation in scientific research had a significant impact on scientific research productivity(P＜0.05). Conclusions It is necessary to stimulate graduates′ interest in scientific research and encourage them to join research project and strengthen the capacity of setting research goals. Also more efforts are needed to optimize research and training environment in terms of tutors and institutions, thus to promote the building of research capacity of graduates to meet the comprehensive requirements for cultivation of medical talents.